2018
DOI: 10.1155/2018/7635957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Varietal Diversity and the Thermal Treatment on the Protein Profile of Peanuts and Hazelnuts

Abstract: Several bu er compositions were compared for their e ciency in protein extraction from both raw and roasted peanut and hazelnut samples, the nal goal being to understand the modi cation of protein solubility upon roasting and maximize the extraction yield. Denaturant conditions provided by urea-TBS bu er resulted in satisfactory extraction yields for both peanut and hazelnut samples, before and after the thermal treatment. In addition, di erent varieties of peanuts and hazelnuts were characterized to highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(53 reference statements)
2
1
0
Order By: Relevance
“…Upon simulated oral–gastric digestion, only up to 10% of the theoretical maximum of protein extraction was attained in the raw and roasted controls for gastric digestion, as shown by the densitometry measurements ( Report S2 as Excel file, Supplementary Materials ). This result is in agreement with the findings of Angelis et al (2018), where extraction using different neutral and slightly basic pH buffers was reported [ 25 ]. In addition, many intact proteins remaining in the food gastric bolus and reaching intestinal mucosa can potentially elicit allergic reactions upon favorable extraction in basic conditions [ 16 , 17 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Upon simulated oral–gastric digestion, only up to 10% of the theoretical maximum of protein extraction was attained in the raw and roasted controls for gastric digestion, as shown by the densitometry measurements ( Report S2 as Excel file, Supplementary Materials ). This result is in agreement with the findings of Angelis et al (2018), where extraction using different neutral and slightly basic pH buffers was reported [ 25 ]. In addition, many intact proteins remaining in the food gastric bolus and reaching intestinal mucosa can potentially elicit allergic reactions upon favorable extraction in basic conditions [ 16 , 17 ].…”
Section: Resultssupporting
confidence: 94%
“…An intense protein band at ~40 kDa, with an accompanying band at 34 kDa, corresponded to an acidic subunit, while bands between 20–23 kDa were associated with basic polypeptide chains of the Cor a 9 protein ( Figure 4 A). This is in agreement with the electrophoretic band patterns of Cor a 9 purified with different buffer systems [ 25 , 26 ]. Up to three minor groups of light polypeptides were also detected, at masses of 19, 18, and 15 kDa.…”
Section: Resultssupporting
confidence: 89%
“…However, despite the importance of Chamaedorea tepejilote Liebm as a food source, very little has been published on the subject; several studies have focused only on the protein content of powdered, dried inflorescences of Chamaedorea tepejilote Liebm, which ranges between 24.19 and 26.72 %; for this reason, pacaya have been considered an important source of protein [1,6,7]. The inflorescences of Chamaedorea tepejilote Liebm are generally consumed once they are cooked, which softens the inflorescence tissue, reduces the bitter taste and reduces enzymatic activity, but thermal treatment could induce modification of the protein structure since it has been reported that heating causes modifications in the structure/conformation of proteins, depending on the thermal processing, the number of complementary treatments and the operating conditions applied [8]. Some authors have indicated that high intensity ultrasound (HIU) also modified the physicochemical properties of protein isolates [9], and some studies have reported that changes in the molecular structure of proteins were observed after HIU treatment, principally in the secondary structure, free sulfhydryl groups and particle size [10].…”
Section: Introductionmentioning
confidence: 99%